Evaluation of Physico-Chemical Parameters of German-Polish Szczecin Lagoon Water - Daniszewski, Piotr (Asian Journal of Chemistry, 2014)
This paper presents the evaluation of physico-chemical parameters of German-Polish Szczecin Lagoon water based on the European Union Water Framework Directive.This approach was formulated in the European Union Water Framework Directive (2000/60/EC), which calls for the protection of water, as well as an environment-friendly and comprehensive approach to water assessment. The research was carried out in the years 2008-2012, between April and October. From each of the three measuring stations located in the water Szczecin Lagoon included the study, two separate water samples were taken for chemical analysis. The Odra (German:Oder) estuary is located at the southern Baltic Sea (German-Polish border). It consists of the Szczecin Lagoon and the Pomeranian Bay. The Szczecin Lagoon (687 km2) can be subdivided into the ‘Large Lagoon’ (Polish:Wielki Zalew) on the Polish territory and the ‘Small Lagoon’ (German: Kleines Haff) on the German side. The studied water Szczecin Lagoon had pH values in the neutral range 7.71 to 7.89. According to the classification of the European Union Water Framework Directive, all water were classified as first class. By analyzing the average annual values, one can note that the pH, O2diss and NO3– concentration showed a relatively small variation in all the investigated water. The total suspended solids in the Szczecin Lagoon, fell into the II class. The Ptot. concentrations in the surface layer of the water Szczecin Lagoon was little differentiated, reaching the levels appropriate for the III quality class. The total phosphorus concentration was 0.43-0.68 mgP dm–3. The concentrations of PO43-diss in the tested waters varied more significantly-corresponding to water quality classes ranging from IV. The concentrations saturation with O2 was 41.7-92.8 %. In the case of nitrogen compounds, nitrates and nitrites values for these indicators fell into the I and II class in all the surveyed water Szczecin Lagoon. The indicator which proves high productivity of the water is the biochemical oxygen demand (BOD5). The level of this indicator in the studied Szczecin Lagoon was at level III. The highest concentration of oxygen in the waters was found in the Szczecin Lagoon (about 8.5 mg O2 dm-3). In the remaining water oxygen levels were similar (still in I class). National Sanitation Foundation Water Quality Index (NSF WQI) used for rating of water quality in Szczecin Lagoon indicates that the quality of water is slightly polluted (WQI = 53.6). The German-Polish Szczecin Lagoon in the southern Baltic Sea is highly eutrophic coastal water that is affected by algae blooms during summer.